Dataset on impact strength, flammability test and water absorption test for innovative polymer-quarry dust composite - Shagwira, Harrison; Mwema, Fredrick; Mbuya, Thomas; Adediran, Adeolu (Data in brief, 2020)
In this article data on impact strength, flammability and water absorption tests for innovative plastic-quarry dust composite is presented. The composites were prepared through moulding with virgin HDPE and PP plastics and quarry dust. The quarry dust was used at 0%, 5%, 20%, 40%, 60% and 80% weight percentages. The prepared samples were characterised for strength, fire resistance and hydrophobic properties using Charpy impact, flammability and water absorption tests respectively. For impact strength test was conducted according to ISO 179–1:2010 (E). The flammability test was conducted according to ASTMD 2863 while the water absorption test was carried out in accordance to ASTM D 570–98. These data illustrate the potential of the plastic quarry dust composite application in construction industry and model for regeneration of waste plastics for green building technologies.